An Analysis Of Dirty Word In Karonese Language - Christina Natalina Saragi; Usman Sidabutar; Ema Ulina Br Ginting; Carolina Pakpahan (Innovative: Journal Of Social Science Research, 2023)
This thesis entitled An Analysis of Dirty Words in Karonese at Tradisional Market Simpang Limun. The objective of the reasearch are intended to identify the types and the most dominat type of dirty words used in karonese at Tradisional Market Simpang Limun. The research was conducted by using descriptive qualitative in the analysis of the dirty words.. The researcher focused only in Karonese people who sells vegetables utterances. The source of the data were Karonese people who sells vegetables and the data from this research are dirty word karo sayings it's in the traditional market Sp. Limun to fellow Karo people. To collect data for "dirty" words to analyze using Jay's theory and Batistella theory. The data of this research were 20 utterances containing taboo words. The findings of this research indicated that the gamers used four types of taboo words and three functions of taboo words. There were found seven types of taboo words are Insult and slur , Scatology,cursing, Profanity,Taboo, Epithits, Vulgarity appeared within Tradisional Market Sp.Limun. Insult and slur 25% ,Cursing 20% Scatology15% ,Profanity10%,Taboo 10%, Epithits10 %,and Vulgarity10 %.This shows that Insult and slur are the most used in Tradisional market at Sp.Limun.